Implementation of Patient Referral Application between Dentist and General Practitioner with Web-Based Specialist - Gusti Ayu Agung Mas Mahadewi; Ratna Wardani; Siti Farida; Rahmania Ambarika (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aim of the research is to dissect implementation of patient referral application between dentist and general practitioner with web-based specialist. The method used in this research is through a qualitative approach. Data collection uses purposive sampling with in-depth interview techniques through questions to 10 informants from dentist, general practitioner, and communication technology specialists accompanied by 2 triangulators. Data collection techniques using observation, interview, documentation, and case study. The data analysis technique was carried out by means of data reduction, data presentation, and conclusion drawing. The results show that the implementation of a systemic patient referral application between dentists and general practitioners with web-based specialists is the right solution in the current era, because the manual referral system has constraints in terms of time, geography, and finance.